Unusual cause of chest pain: Thoracic aorta calcification - Rai, Deependra Kumar; Kumar, Abhishek; Anupam, Chinki (Eastern Journal of Medical Sciences, 2016)
A 40-year-old woman treated for pulmonary tuberculosis presented with chest pain which was aggravated with exertion without radiation. Chest X-ray shows widening of mediastinum, old healed, and calcified parenchymal lesion. Computed tomography scan showed annular calcification of aorta (solar eclipse sign) with significant narrowing of aorta. The patient responded well with vasodilator nifedipine, and almost 75% reduction in symptoms was seen after 1 month of the treatment.